2016
DOI: 10.1155/2016/2674954
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Radiotherapy versus Radical Prostatectomy with Limited Lymph Node Sampling for High-Grade Prostate Adenocarcinoma

Abstract: Purpose. To compare oncologic outcomes for patients with Gleason score (GS) ≥ 8 prostate adenocarcinoma treated with radical prostatectomy (RP) versus external beam radiotherapy combined with androgen deprivation (RT + ADT). Methods. Between 2001 and 2014, 121 patients with GS ≥ 8 were treated at our institution via RT + ADT (n = 71) or RP (n = 50) with ≥ 1 year of biochemical follow-up. Endpoints included biochemical failure (BF), distant metastasis, and initiation of salvage ADT. Results. The RT + ADT group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…According to our analysis, the types of RT could affect the survival and progression of patients. In fact, several RCT demonstrated a BRFS benefit to EBRT + BT over EBRT [45][46][47] and several retrospective studies have reported that EBRT + BT brought better outcome than RP on BRFS [39,48,49] and MFS [35,36,38,50]. It was not difficult to find that EBRT + BT had strong control over disease progression, which might lead to better CSS for patients treated with EBRT + BT than patients treated with RP.…”
Section: Discussionmentioning
confidence: 99%
“…According to our analysis, the types of RT could affect the survival and progression of patients. In fact, several RCT demonstrated a BRFS benefit to EBRT + BT over EBRT [45][46][47] and several retrospective studies have reported that EBRT + BT brought better outcome than RP on BRFS [39,48,49] and MFS [35,36,38,50]. It was not difficult to find that EBRT + BT had strong control over disease progression, which might lead to better CSS for patients treated with EBRT + BT than patients treated with RP.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies 15 16 17 19 21 22 24 25 27 28 provided data of EBRT modality, such as conventional EBRT, three dimensional conformal radiation therapy, and intensity modulated radiation therapy. Radiation dosage was only mentioned in 15 15 16 17 18 19 20 21 22 23 24 25 27 28 29 31 of 17 studies and mostly ranged from 60 to 80 gray (Gy, J kg −1 ). In addition, considerable variability was found in the use of adjuvant or salvage therapies, regardless of the modality or duration.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies included, 16 were retrospective 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 and one was a RCT. 15 The RCT scored three out of five points (considered as high quality) according to the Jadad Scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fakat yüksek riskli olgularda suboptimal PSA kontrolü ve sağ kalım oranları elde edilebilmektedir. Bu grup hastalarda, çoğu merkezde iki tedavi yaklaşımından biri seçilmektedir: cerrahi (RRP) veya radyoterapi (RT) + androjen deprivasyon tedavisi (ADT) (4,5).…”
unclassified